PENGARUH RISIKO BISNIS DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Kevin Andreas B; Ricardo Suhendra Wirjawan (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to examine the effect of managerial ownership, corporate social responsibility disclosure, return on asset, price book value, business risk, size company, debt equity ratio to the firm value in non-financial companies listed on Indonesia Stock Exchange. The population of this research is non-financial companies listed on Indonesia Stock Exchange during 2018 to 2020. The sample was selected using purposive sampling method which consisting 117 companies and 351 data selected as research sample. This study uses multiple regression and hypothesis testing as analysis method. The empirical result of this research indicates return on asset, price book value, and debt equity ratio has effect to firm value. While managerial ownership, corporate social responsibility disclosure, business risk, and company size has no effect to firm value.